1985
DOI: 10.1021/bi00345a012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the kinetics and mechanism of the papain-catalyzed hydrolysis of esters and thiono esters

Abstract: The kinetic constants for the papain-catalyzed hydrolysis of the methyl thiono esters of N-benzoylglycine and N-(beta-phenylpropionyl)glycine are compared with those for the corresponding methyl ester substrates. The k2/Ks values for the thiono esters are 2-3 times higher than those for the esters, and both show bell-shaped pH dependencies with similar pKa's (approximately 4 and 9). The k3 values for the thiono esters are 30-60 times less than those for the esters and do not exhibit a pH dependency. Solvent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Comparison of these structures showed that the 2'-OH-of the ribityl side chain of FAD would have to be rotated away from the carbonyl oxygen of the substrate to accommodate the larger sulfur atom. While some enzymes can tolerate such substitution with little effect (Storer & Carey, 1985), replacement of C=O by C=S generally significantly slows catalysis [e.g., Wlassics et al (1988) and Anderson et al (1990)l. Thus, the comparatively weak binding of 2-azadithiooctanoyl-CoA, the low turnover with dithiooctanoyl-CoA, and the molecular modeling results are consistent with a tight interaction between the substrate carbonyl oxygen and its binding pocket in the medium chain dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of these structures showed that the 2'-OH-of the ribityl side chain of FAD would have to be rotated away from the carbonyl oxygen of the substrate to accommodate the larger sulfur atom. While some enzymes can tolerate such substitution with little effect (Storer & Carey, 1985), replacement of C=O by C=S generally significantly slows catalysis [e.g., Wlassics et al (1988) and Anderson et al (1990)l. Thus, the comparatively weak binding of 2-azadithiooctanoyl-CoA, the low turnover with dithiooctanoyl-CoA, and the molecular modeling results are consistent with a tight interaction between the substrate carbonyl oxygen and its binding pocket in the medium chain dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Miller et al (21) have shown that removal of the Gln215 side chain, the only active-site functional group within proximity of O2 of the bound ligand, is inconsequential for decarboxylase activity. It is predictable from these observations that 2-thioUMP would have approximately the same affinity as UMP, as there appears to be ample accommodation for the larger CϭS group, which is typically 0.4 Å longer than a CϭO double bond (22). It is not evident, however, why 2-thioOMP does not bind and undergo decarboxylation if it occupies the same orientation as UMP as seen in the crystal structures, and that projected for OMP by the mechanism in Fig.…”
Section: ϫ7mentioning
confidence: 69%
“…Collapse of the tetrahedral intermediate formed after solvent attack will reform the covalent adducts but may result in loss of sulfur since this would be a good leaving group (20). Such sulfur/oxygen exchange from an enzyme-dithio-HMG-CoA adduct, followed by cleavage of the covalent linkage to enzyme, would produce unsubstituted HMGCoA.…”
Section: Inhibition Of Hmg-coamentioning
confidence: 99%